ANALYSIS OF FACTORS INHIBITING THE APPLICATION OF THE MIMICRY MEMORIZATION METHOD IN MASTERING STUDENT MUFRODAT CLASS VII MTS AL-ITTIHADIYAH MAMIYAI - Manurung, Sartika Alpianti; Al-Rasyid, Harun (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
Based on the theory, the mimicry memorization method is one of the methods that is considered effective in learning mufrodat because it is based on pronunciation and memorization. The application of the mimicry memorization method in learning mufrodat is not always effective even though the theory says so, this is due to several problems that cause the learning objectives not to be achieved and this often happens in educational institutions, one of which is MTs Al-Ittihadiyah Mamiyai Medan. The purpose of this research is to find out the inhibiting factors, as well as find solutions to the problems that occur in the field. This research uses a descriptive qualitative approach. Data were obtained in several ways, namely, literature review, in-depth interviews and participatory observation. The data were analyzed in four ways, namely, reduction, presentation, conclusion drawing and triangulation. The results of this study indicate that there are two inhibiting factors in the form of internal and external as well as alternative solutions that can be done in each problem that occurs